PERFORMANCE OF THE GAIT IN INDIVIDUALS WITH HTLV-1: SYSTEMATIC REVIEW - Santana, Mateus Evangelista do Amparo; Pereira, Livia Aguiar; Monteiro, Rafael; Fonseca, Erika Pedreira (Revista Pesquisa em Fisioterapia, 2017)
HTLV-1 is frequently associated with myelopathy/tropical spastic paraparesis (HAM/TSP), which in turn brings several functional alterations to the individual, including changes in gait. Objective: To systematize the scientific findings on the temporo-spatial gait parameters in individuals with HTLV-1. Methodology:  This is a systematic review of the scientific literature. The primary search of the articles was performed in the Pubmed, Scielo and Bireme databases, and observational studies were included that evaluated gait changes in individuals with HTLV-1. The search strategy was conducted by two researchers apart and the divergences resolved by consensus.  Results:  Firstly, it has found 40 studies and considering them, it was included two studies that investigated the changes in gait performance among the individuals with HTLV-1, within a total of 97 individuals. Conclusion:  This systematic review identified changes in gait pattern among individuals with tropical spastic paraparesis/myelopathy associated to HTLV-1; functional changes in muscle groups of the lower limbs and slowing gait speed are among the main findings, but the lack of published work on the subject makes it difficult to access information. Therefore, it is suggested that new approaches be made for a better understanding of this topic.